Beginning Windows Phone 7 application development : building Windows phone applications using Silverlight and XNA - Lecrenski, Nick; Watson, Karli; Fonseca-Ensor, Robert (Wrox beginning guides., 2011)
Discover the core concepts essential for developing apps for Windows Phone Silverlight and XNA provide you with a powerful development platform and key tools for programming Windows Phone 7 series applications. This book offers a foundation for using the tools required for Windows Phone 7 development, including Visual Studio 2010 Express Edition, the Windows Phone 7 Series SDK, and Silverlight. Experienced authors provide you with detailed coverage on developing accordingly for an application's lifetime, accessing cloud services, and developing notification services. Explains how to use the mos.